Effects of Combined Aerobic-Strength Training vs Fitness Education Program in COPD Patients - Rinaldo, Nicoletta; Bacchi, Elisabetta; Coratella, Giuseppe; Vitali, Francesca; Milanese, Chiara; Rossi, Andrea; Schena, Federico; Lanza, Massimo (International Journal of Sports Medicine, 2017)
We compared the effects of a new physical activity education program approach (EDU), based on a periodically supervised protocol of different exercise modalities vs traditionally supervised combined strength-endurance training (CT) on health-related factors in patients with stable chronic obstructive pulmonary disease (COPD). Twenty-eight COPD patients without comorbidities were randomly assigned to receive either EDU or CT. CT was continuously supervised to combine strength-endurance training; EDU was taught to progressively increase the rate of autonomous physical activity, through different training modalities such as Nordic walking, group classes and circuit training. Body composition, walking capacity, muscle strength, flexibility and balance, total daily energy expenditure and quality of life were evaluated at baseline, after 28 weeks training period (3d/week) and after a 14-week follow-up. No adverse events occurred during the interventions. After training, CT and EDU similarly improved walking capacity, body composition and quality of life. However, after 14 weeks of follow-up, such improvements were not maintained. Only in CT, muscle strength and flexibility improved after training but returned to baseline after follow-up. EDU, similar to CT, can effectively and safely improve health-related parameters in COPD patients. EDU could be an attractive alternative to traditional supervised training for improving quality of life in COPD patients.
Keywords: aerobic training; strength training; chronic obstructive pulmonary disease; quality of life; walking capacity; muscle strength; bone mineral content